Analisis Sistem Antrian untuk Optimalisasi Layanan Teller Bankaltim di Samarinda - Tasha Octavia Balqis; Zainal Ilmi; M. Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this research is to analyze the service system provided by BanKaltim teller and to know the optimal teller number so as not to cause long queue by using M / M / S model. Methods of data collection by making observations and recording directly on the object of research to obtain the necessary data in research and to complement the data that has been obtained, the authors conducted an unstructured interview with both the teller and customers BanKaltim. Method of data analysis using formula 2 M / M / S. The equation used for this model is the probability that no consumer is in the system, the probability that a consumer enters the system and has to wait to be served, the average number of consumers in the system and the queues respectively, the average time in the system and the average Queue time respectively, utility level of service facility. The results of this study indicate that the service system teller on BanKaltim Sub-Branch Office Juanda with 2 tellers is still not optimal. It can be concluded that the optimal teller number that must be operated by BanKaltim Branch Juanda Maid is 3 teller.Keywords: Service Optimization, Queue System Analysis